2019
DOI: 10.1186/s40945-019-0061-8
|View full text |Cite
|
Sign up to set email alerts
|

Is there a relationship between self-efficacy, disability, pain and sociodemographic characteristics in chronic low back pain? A multicenter retrospective analysis

Abstract: Background Pain-related self-efficacy is defined as the beliefs held by people with chronic pain that certain activities can be carried out despite the pain. Poor self-efficacy is an obstacle to the recovery and predicts long-term disability. The aims of this study are to investigate the prevalence of poor pain self-efficacy in Italian subjects with chronic low back pain (LBP), and to inquire the relationships between self-efficacy, disability, pain, and main demographic and clinical characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 71 publications
7
25
0
Order By: Relevance
“…This result implies that the association between level of disability and job-seeking self-efficacy may be non-linear. The positive association between higher education level and higher self-efficacy (Ferrari et al, 2019) was also significant in the study, especially for those with post-secondary education. Similarly, people with self-reported professional skills had significantly higher self-efficacy than did those without.…”
supporting
confidence: 55%
“…This result implies that the association between level of disability and job-seeking self-efficacy may be non-linear. The positive association between higher education level and higher self-efficacy (Ferrari et al, 2019) was also significant in the study, especially for those with post-secondary education. Similarly, people with self-reported professional skills had significantly higher self-efficacy than did those without.…”
supporting
confidence: 55%
“…Evidence suggests that there are important clinical and experiential pain differences attributed to sex and gender [ 71 , 72 ]. While the reliability estimates were high in both men and women, a disaggregated analysis by sex shows that Physical Functioning, Social Functioning, Bodily Pain, Emotional Wellbeing, and General Health Perception of the SF-36 subscales were moderately correlated with PSEQ-Am among men with LBP.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism underlying this difference between men and women is unclear. Such a difference in the correlation between PSEQ-Am and SF-36 subscales could be related to sex or gender role differences in pain perception and expression [ 71 , 72 ]. Future studies involving Rasch analysis to look at differential item functioning (DIF) of the tool based on sex of the participants in the Ethiopian sample of LBP may help to understand these sex or gender differences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CLBP is attributed to intricate biopsychosocial mechanisms and multiple risk factors [3,4]. Several studies have evaluated the relationship between CLBP and self-efficacy (individual's confidence in their ability to perform a task) and found that cognitive tests, such as assessment of functional self-efficacy, have greater explanatory power than specific pain-related assessments [5][6][7][8][9]. In addition, associations were found between low self-efficacy and higher disability rates [7,10].…”
Section: Introductionmentioning
confidence: 99%